A coupled system of fractional q-integro-difference equations with nonlocal fractional q-integral boundary conditions - Suantai S. (Springer Publishing Company, 2015)
© 2015, Suantai et al.; licensee Springer. In this paper, we investigate the existence and the uniqueness of solutions for coupled and uncoupled systems of fractional q-integro-difference equations with nonlocal fractional q-integral boundary conditions. The existence and the uniqueness of the solutions are established by using the Banach contraction principle, while the existence of solutions is derived by applying Leray-Schauder’s alternative. Examples illustrating our results are also presented.